Dignitaries-Abboud, Ferik Ibrahim-0003
Sudan President El Ferik Ibrahim Abboud became the first foreign chief of state to visit the Fresno State campus when he took a whirlwind tour of the college on October 10, 1961. President Abboud personally requested the state department to visit Fresno and the college. From the moment he stepped off the plane at the Fresno Air Terminal, the president's personal charm took effect. he accompanied on the tour by four cabinet members, the Sudanese ambassador to the United States, personal aides, state department officials and numerous members of the Sudanese and American press. After inspecting cotton picking machinery and the college agriculture department, the president took short car tour of the academic campus. Following an informalreception, President Abboud presented the college president, Dr. Arnold E. Joyal, with a 20 inch gold trophy as a gift to the college. It was engraved in English and Arabic. ALL SMILES, President Abboud accepts sugar for his tea from student hostess Jane Pippert. At the informal reception, relaxed and responsive, he talked with one and all.